The impact of interest rate changes on the Islamic foreign exchange forward in the Malaysian derivative market - Nor Azmah Md. Arif,; Ruhaini Muda,; Md. Mahmudul Alam,; Saadiah Mohamad, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Islamic foreign exchange forward plays a significant role to mitigate various foreign currency exchange risks. The main challenge that impedes the development and operation of the Islamic foreign exchange forward as a hedging instrument is the behaviour of relying on existing conventional framework with core conception of relying on interest rate and excessive risk taking. This study utilized monthly data from April 2004 to October 2017 of the Malaysian derivatives market. This study found that in the absence of an alternative profit-rate related benchmark and cross border activities, Islamic banks are constrained to use the interest rate benchmark. In the short run, both medium term (6-months) and longer term (12-months) tenures indicate faster speed of adjustment possibility due to higher trading volume and less demand for the medium term for the Islamic foreign exchange forward contract. It implies a need of the Islamic foreign exchange forward as a longer term hedging instrument and not for a short term speculation and risk-taking purposes, as prohibited by shariah.